The perception of inbound tourist towards the cleanliness of Tunku Abdul Rahman Park Sabah / Fennie Petrus and Mohd Asjad Lami - Petrus, Fennie; Lami, Mohd Asjad (2013)
Tunku Abdul Rahman Parks is the one of the tourist attraction for the tourism activity near the Kota Kinabalu Sabah. However, in the recent year it been reported in the news paper that the islands are slowly and gradually are surrounded by the rubbishes from the littering activity. The Anti Litter Bug are already implemented however it does not a successful to curb the issues regarding this issues especially in the Tunku Abdul Rahman Parks which focusing in Pulau Manukan, Pulau Mamutik and Pulau Sapi. From the previous study that had been done regarding the littering issues and Anti Litter Bug Campaign, some of the factors that contributes to the ineffectiveness is the lack of enforcement even tough the law and policy are already been implemented. The study examines the enforcement that will contribute to the perception of inbound tourist towards the cleanliness of Tunku Abdul Rahman Parks. A set of 100 questionnaires area distributed at the three islands selected and at the Jesselton Point Jetty. In the questionnaires, the respondents are asked about their profiles, the cleanliness at the islands also the enforcement by the government and authorized entity in Tunku Abdul Rahman Parks. The results based on the data analysis shows that the factors that mention above did affected the perception of inbound tourist towards the cleanliness at the Tunku Abdul Rahman Parks. With, low of enforcement by the government and the authorized entity in Tunku Abdul Rahman Parks.